Tools for classification of growing/non-growing bacterial colonies using laser speckle imaging - Balmages, Ilya; Liepins, Janis; Zolins, Stivens; Bliznuks, Dmitrijs; Broks, Renars; Lihacova, Ilze; Lihachev, Alexey (Frontiers in Microbiology, 2023)
Prior research has indicated the feasibility of assessing growthassociated activity in bacterial colonies through the application of laser speckle imaging techniques. A subpixel correlation method was employed to identify variations in sequential laser speckle images, thereby facilitating the visualization of specific zones indicative of microbial growth within the colony. Such differentiation between active (growing) and inactive (nongrowing) bacterial colonies holds considerable implications for medical applications, like bacterial response to certain drugs or antibiotics. The present study substantiates the capability of laser speckle imaging to categorize bacterial colonies as growing or nongrowing, a parameter which nonvisible in colonies when observed under white light illumination.